Feasibility of surgical management in patients with mammary tuberculosis-study of 100 cases. (TAJ: Journal of Teachers Association, 2018)
Tuberculous mastitis is a rare entity in patients with mammary disease even in countries where incidence of tuberculosis is high. In Bangladesh, TB is an endemic disease but breast tuberculosis is rarely reported. Its clinical patterns and treatment strategies are changing day by day. With this study, we aimed to analyze the role of surgery in diagnosis and treatment of hundred (100) cases received care for tuberculous mastitis at the Chest Disease Hospital, Rajshahi, from July’ 2012 to July’ 2016. This is a prospective nonrandomized descriptive study. Diagnosis was made in all patients initially by cytological examination from suspected lesions, which revealed typical tuberculous lesions. In all the patients the diagnosis was confirmed by biopsy of the lesion (open biopsy or core cut biopsy) with histological examination and detection of acid fast bacilli in discharge by Gene x-pert test and Z-N staining to exclude idiopathic granulomatous mastitis, malignancy and very rare concomitant malignancy. Medical therapy with anti-tubercular drugs (ATT) ranging from 9 to 12 months with follow up monthly was the mainstay of treatment. Surgical intervention reserved for selected refractory cases (36%). Extension of anti-tubercular therapy from 9 to 12 or 18 months required in fifty-eight(58) patients on the basis of slow clinical response. Complete resolution obtained in 92 patients but residual tiny mass in eight patients confirmed by repeated FNAC or biopsy to be fibrotic. Surgery play an essential role both in diagnosis and treatment of tubercular mastitis in addition with ATT but beware about unnecessary surgical intervention as majority of patients cured with only ATT.TAJ 2014; 27(1): 44-49